2023
DOI: 10.1002/pc.27716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lamination sequence and warhead shape on impact resistance of fiber‐metal laminates

Gang Wei,
Chenyu Hao,
Jingyu Ai
et al.

Abstract: In this work, the failure mode and ballistic protection capability of the carbon fiber aluminum alloy laminated target plate under the impact of high‐speed projectile body were studied by ballistic impact test. The effects of the lamination sequence and warhead shape difference on the impact resistance of the laminated aluminum alloy and carbon fiber laminates were analyzed. Two kinds of projectile bodies, flat and oval head, were used to carry out multiple high‐speed impact experiments on four groups of targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Rajesh et al 29 carried a comparative study of carbon fiber and AA 6061 based FMLs against carbon fiber reinforced composite and observed that the FMLs showed improved impact resistance, enhanced tensile strength, increased flexural capability, microstructural evolution, and surface composition. Wei et al 30 studied the effect of lamination sequence and warhead shape on impact resistance of the laminated aluminum alloy and carbon fiber laminates. Flat and oval head projectiles were used to carry out multiple high‐speed impact experiments on four groups of targets with different stacking sequences.…”
Section: Research Gap Addressed In the Papermentioning
confidence: 99%
“…Rajesh et al 29 carried a comparative study of carbon fiber and AA 6061 based FMLs against carbon fiber reinforced composite and observed that the FMLs showed improved impact resistance, enhanced tensile strength, increased flexural capability, microstructural evolution, and surface composition. Wei et al 30 studied the effect of lamination sequence and warhead shape on impact resistance of the laminated aluminum alloy and carbon fiber laminates. Flat and oval head projectiles were used to carry out multiple high‐speed impact experiments on four groups of targets with different stacking sequences.…”
Section: Research Gap Addressed In the Papermentioning
confidence: 99%